EFFECTS OF APPLIED MAGNETIC-FIELD ON THE ENERGY-LEVELS OF SHALLOW DONORS IN A PARABOLIC QUANTUM-DOT - ELSAID, M (Elsevier Science Bv, 1994)
The effects of an applied magnetic field of arbitrary strength on shallow donor impurity states in a parabolic quantum dot are theoretically studied. The shifted 1/N-expansion method is used to solve the impurity effective-mass Hamiltonian. The transition energies between the impurity ground and the excited states (2P +/-) are also calculated.
Keywords: States; Expansion; Electron; Gaas